-3+5=-3(9x+1)

Simple and best practice solution for -3+5=-3(9x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3+5=-3(9x+1) equation:


Simplifying
-3 + 5 = -3(9x + 1)

Combine like terms: -3 + 5 = 2
2 = -3(9x + 1)

Reorder the terms:
2 = -3(1 + 9x)
2 = (1 * -3 + 9x * -3)
2 = (-3 + -27x)

Solving
2 = -3 + -27x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '27x' to each side of the equation.
2 + 27x = -3 + -27x + 27x

Combine like terms: -27x + 27x = 0
2 + 27x = -3 + 0
2 + 27x = -3

Add '-2' to each side of the equation.
2 + -2 + 27x = -3 + -2

Combine like terms: 2 + -2 = 0
0 + 27x = -3 + -2
27x = -3 + -2

Combine like terms: -3 + -2 = -5
27x = -5

Divide each side by '27'.
x = -0.1851851852

Simplifying
x = -0.1851851852

See similar equations:

| 1b+-9=36 | | 5x^3-16x^2-21x=0 | | 7.5/4.3=X/3.75 | | (-8)-3(-5)= | | 40+15+0.25(100)=45+0.35(100) | | 2/5y=1/5x+8/5 | | x^3+2x=144 | | 7.50x+y=395 | | -7-4(1+9d)=20 | | 1/3+x=1/2 | | 40+15+0.25(10)=45+0.35(10) | | 2a+6=-3a+2 | | 7(t+4)-3(l+t)=19 | | x^2-4=2x(x-2) | | y-13=-20 | | 2a+6=3a-2 | | 16+-9=36 | | x^3+2x^2=144 | | -7h+4=-2h-16 | | 9-(-11a)-7=-1 | | x(x+28)=196 | | (2x-5)(7x+1)(3x-7)=0 | | 1t+12=-18 | | h-4/5=56/5 | | -y+18=-3 | | 8+10r-2=9r+12-2r | | -7y+4x=18 | | 97+5.9=11.77 | | 40+15+0.25x=45+0.35x | | h-4/5=111/5 | | -3.1=4.75-1e | | -8(3k-6)=18+2k |

Equations solver categories